2011
DOI: 10.1128/iai.00863-10
|View full text |Cite
|
Sign up to set email alerts
|

Francisella tularensisSchu S4 O-Antigen and Capsule Biosynthesis Gene Mutants Induce Early Cell Death in Human Macrophages

Abstract: Francisella tularensis is capable of rampant intracellular growth and causes a potentially fatal disease in humans. Whereas many mutational studies have been performed with avirulent strains of Francisella, relatively little has been done with strains that cause human disease. We generated a near-saturating transposon library in the virulent strain Schu S4, which was subjected to high-throughput screening by transposon site hybridization through primary human macrophages, negatively selecting 202 genes. Of spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
182
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(201 citation statements)
references
References 73 publications
17
182
1
1
Order By: Relevance
“…Francisella strains with mutations in the wbt locus are attenuated during infection of both macrophages (130,135,221) and mice (129,153,204,221,232). Furthermore, mutants lacking genes necessary for O-antigen production that are outside the wbt locus are also attenuated for intracellular replication and in vivo virulence compared to the wild type (130).…”
Section: Complement and Antibodymentioning
confidence: 98%
See 4 more Smart Citations
“…Francisella strains with mutations in the wbt locus are attenuated during infection of both macrophages (130,135,221) and mice (129,153,204,221,232). Furthermore, mutants lacking genes necessary for O-antigen production that are outside the wbt locus are also attenuated for intracellular replication and in vivo virulence compared to the wild type (130).…”
Section: Complement and Antibodymentioning
confidence: 98%
“…This is important to note, since recent evidence has suggested that the O antigen and capsule of Francisella are structurally similar, with the capsule consisting of a polymer of O-antigen tetrasaccharide subunits (9) as well as a glycoprotein component termed a "capsulelike complex" (18). As such, some mutants deficient in LPS O-antigen production are also impaired in the production of capsule (9,130), including specific wbt operon mutants (wbtA, wbtC, wbtM, and wbtI). wbtK and lpxL mutants lose the ability to synthesize LPS O antigen but maintain the polysaccharide capsule (9).…”
Section: Complement and Antibodymentioning
confidence: 99%
See 3 more Smart Citations